2007
DOI: 10.1245/s10434-006-9258-7
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Mapping in Colon Cancer: Current Status

Abstract: Background: The primary role of sentinel lymph node (SLN) mapping in colon cancer is to increase the accuracy of nodal staging by identifying those lymph nodes with the greatest potential for harbouring metastatic disease. Ultrastaging techniques aim to identify the otherwise undetected metastases. Until now, no consensus exists as to the most optimal procedure in patients with colon cancer.Methods: A systematic literature search on the value of different SLN mapping techniques in patients with colon cancer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 66 publications
(231 reference statements)
1
22
1
1
Order By: Relevance
“…Importantly, the SLN identification process for colon cancer can be done before the tumour is resected (in vivo) or afterwards (ex vivo) [50]. In addition, lymphatic mapping for colon cancer is typically performed using blue dye rather than the combination of radiocolloid/blue dye that is recommended for breast cancer and melanoma SLN mapping [51,52]. A recent systematic review on the current status of sentinel node mapping in colon cancer which reported that the sentinel node identification rate, using blue dye alone, was between 71% and 100%, and the false negative rate ranged between 0% and 54% [51].…”
Section: Lymphatic Mapping and Ultrastaging Lymph Nodes In Colon Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the SLN identification process for colon cancer can be done before the tumour is resected (in vivo) or afterwards (ex vivo) [50]. In addition, lymphatic mapping for colon cancer is typically performed using blue dye rather than the combination of radiocolloid/blue dye that is recommended for breast cancer and melanoma SLN mapping [51,52]. A recent systematic review on the current status of sentinel node mapping in colon cancer which reported that the sentinel node identification rate, using blue dye alone, was between 71% and 100%, and the false negative rate ranged between 0% and 54% [51].…”
Section: Lymphatic Mapping and Ultrastaging Lymph Nodes In Colon Cancermentioning
confidence: 99%
“…In addition, lymphatic mapping for colon cancer is typically performed using blue dye rather than the combination of radiocolloid/blue dye that is recommended for breast cancer and melanoma SLN mapping [51,52]. A recent systematic review on the current status of sentinel node mapping in colon cancer which reported that the sentinel node identification rate, using blue dye alone, was between 71% and 100%, and the false negative rate ranged between 0% and 54% [51]. In the two studies (n ¼ 25, 57) that used both radiocolloid and blue dye, the identification rate was 88% and 98% and the false negative rate was 45% and 17% [51].…”
Section: Lymphatic Mapping and Ultrastaging Lymph Nodes In Colon Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Em recentes revisões de trabalhos relevantes, levando-se em consideração diferentes técnicas, a identificação de linfonodo-sentinela variou de 71 a 100% 18,19 .…”
unclassified